2012
DOI: 10.1159/000341633
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Basophil Research: Do Basophils Initiate and Perpetuate Type 2 T-Helper Cell Responses?

Abstract: Basophils account for only 0.1–1% of all peripheral blood leukocytes. They were considered to be a redundant cell type for a long time. However, several findings show a non-redundant role for basophils in type 2 T-helper cell (Th2) immune responses in helminth infections, allergy and autoimmunity. Both immunoglobulin-E-dependent and -independent pathways have been described to contribute to basophil activation. In addition, several recent studies reported that basophils can function as antigen-presenting cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 162 publications
(131 reference statements)
0
21
0
Order By: Relevance
“…Numerous studies have demonstrated that basophils not only play crucial roles in the effector phase, but also critically participate in the initiation of Th2-centered immune responses (7)(8)(9)(10)(11). Using an ovalbumin (OVA)-induced allergic airway inflammation mouse model, we previously showed that basophils acted as a primary inducer of the Th2 immunity, evident by increased OVA-specific immunoglobulin E (OVA-sIgE) and IL-4 levels both in serum and bronchial alveolar lavage fluid (BALF), and increased proportion of Th2 cells in the spleen after transfusion of lung basophils derived from OVA-challenged mice into wild-type (WT) mice (12).…”
Section: Asthma Is Characterized By Increased Airway Submucosal Infilmentioning
confidence: 99%
“…Numerous studies have demonstrated that basophils not only play crucial roles in the effector phase, but also critically participate in the initiation of Th2-centered immune responses (7)(8)(9)(10)(11). Using an ovalbumin (OVA)-induced allergic airway inflammation mouse model, we previously showed that basophils acted as a primary inducer of the Th2 immunity, evident by increased OVA-specific immunoglobulin E (OVA-sIgE) and IL-4 levels both in serum and bronchial alveolar lavage fluid (BALF), and increased proportion of Th2 cells in the spleen after transfusion of lung basophils derived from OVA-challenged mice into wild-type (WT) mice (12).…”
Section: Asthma Is Characterized By Increased Airway Submucosal Infilmentioning
confidence: 99%
“…Recent studies concentrated on the investigation of the role of basophils during adaptive immune responses [215]. These studies were complicated due to functional discrepancies between human and mouse basophils [215].…”
Section: T Cell Model Systems For Allergy Researchmentioning
confidence: 99%
“…These studies were complicated due to functional discrepancies between human and mouse basophils [215]. It has been shown that mouse basophils can act as APC [216,217], whereas human basophils were not able to internalize and present allergen to allergen-specific T cells [218] and therefore did not induce T cell proliferation [218,219].…”
Section: T Cell Model Systems For Allergy Researchmentioning
confidence: 99%
“…Purified basophils (BMB) were overnight cultured under five different conditions: medium, IL-18+IL-33, TSLP, IgE, or CD200R3. These conditions mimic different routes of activation of basophils [289]. The five different conditions resulted in distinct basophil phenotypes.…”
Section: Function Of Basophils Is Impaired In Old Mice In a Microbiotmentioning
confidence: 99%
“…It is, however, largely unknown what effect age has on basophil differentiation and function. Basophils are granulocytes which are involved in mounting and perpetuating Th2-mediated responses [289]. Basophils are an important source of IL-4 and IL-13, which direct the immune response towards Th2 type responses [290].…”
mentioning
confidence: 99%